Transition to peptide‐based diet improved enteral nutrition tolerance and decreased healthcare utilization in pediatric home enteral nutrition. Issue 3 (19th July 2021) - Mohamed Elfadil, Osman; Steien, Dana B.; Narasimhan, Ramya; Velapati, Saketh R.; Epp, Lisa; Patel, Ishani; Patel, Jalpan; Hurt, Ryan T.; Mundi, Manpreet S.
Abstract: Background: Home enteral nutrition (HEN) use continues to increase in children unable to meet nutritional needs through oral intake. Some patients do not tolerate standard polymeric formula (SPF), which may lead to malnutrition. Use of peptide‐based diet (PBD) has demonstrated benefits in adults, however there remains a paucity of data in pediatric population. Methods: Retrospective review of medical records of children receiving HEN between October 2015 and October 2019 was conducted. Nutrition, tolerance, and healthcare utilization was tracked through May 2020. Children receiving PBD as initial formula or transitioned to PBD from SPF were included. Our objective was to assess gastrointestinal tolerance and impact on healthcare utilization in children receiving PBD. Results: During study period, 30 children (mean age, 9 ± 5.44 years; 20 of 30 [66.7%] male) utilized PBDs. Twenty‐one patients started PBD directly with malnutrition as primary indication. Nine patients transitioned from SPF to PBD, most often due to intolerance of SPF (66%). After transition to PBD, no symptoms were reported in 6 of 9 (66.7%) patients, and symptoms of SPF intolerance resolved in 4 of 9 (44.5%) patients. Healthcare utilization declined significantly after transition to PBD, including mean numbers of emergency room visits (0.78 ± 1.09 to 0.11 ± 0.33; P = .025), provider visits (1.67 ± 1.32 to 0.56 ± 0.73; P = .007), and phone calls (1.22 ± 1.39 to 0.33 ± 0.50; P = .026). Conclusions: PBD is well tolerated and can result in significant reduction in healthcare utilization in children intolerant to SPF.